2004
DOI: 10.1002/ijc.20326
|View full text |Cite
|
Sign up to set email alerts
|

PIBF (progesterone induced blocking factor) is overexpressed in highly proliferating cells and associated with the centrosome

Abstract: PIBF was previously identified as a 34 kDa immunomodulatory molecule secreted by pregnancy lymphocytes and is thought to play a crucial role in preventing rejection of the embryo by the maternal immune response. Recent data suggested that PIBF protein was also expressed by the progesterone receptor (PR) positive MCF-7 breast tumor cell line. Given the notion that a number of proteins shown to be involved in tumorigenesis are associated with the centrosome and disturbed centrosome function causes unequal segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 33 publications
1
103
0
7
Order By: Relevance
“…Recently, overexpression of this gene was associated with breast cancer and highly proliferating cells. The PIBF1 protein is associated with the centrosome (28,29). Notably, loss of progesterone receptor in meningioma patients is correlated with tumor grade and a poor prognosis (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, overexpression of this gene was associated with breast cancer and highly proliferating cells. The PIBF1 protein is associated with the centrosome (28,29). Notably, loss of progesterone receptor in meningioma patients is correlated with tumor grade and a poor prognosis (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing analysis showed that the 52 clones represented 30 distinct antigens (Table 1). Of these 30 antigens, one is the CT antigen CAGE protein, and the other 13 antigens, which had previously been reported to be involved in tumorigenesis or suspected to be involved in tumour progression, including CDC37 (Stepanova et al, 2000), MIF (Li et al, 2004), galectin 4 (Huflejt and Leffler, 2004), galectin 8 (Bidon-Wagner and Le Pennec, 2004), PINCH (WangRodriguez et al, 2002), SPRY2 (Lee et al, 2004a), HSPCA (Becker et al, 2004;Huang et al, 2004b), transgelin 2 (Shields et al, 2002), HDAC2 , H factor (Junnikkala et al, 2000), AAT (Huang et al, 2004a), B factor (Perou et al, 1999), PIBF (Lachmann et al, 2004). Three other antigens (SR140 protein, SFRS2IP, RNPC2) may be involved in the regulation of alternative mRNA splicing, PSMA7 is related to hepatitis B and hepatitis C viral replication (Zhang et al, 2000;Kruger et al, 2001), and the remaining 12 antigens have no known association with cancer or hepatitis B or hepatitis C.…”
Section: Serex Defined Hcc-associated Antigensmentioning
confidence: 99%
“…There is an immunomodulatory protein known as the progesterone induced blocking factor (PIBF) that is overexpressed in highly proliferating cells [1]. The parent compound, which measures 90 kDa, resides in the nucleus at a centrosomal position [1].…”
Section: Introductionmentioning
confidence: 99%
“…The parent compound, which measures 90 kDa, resides in the nucleus at a centrosomal position [1]. This protein seems to be unique in that it shows no significant amino acid sequence homology with any known protein [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation